Factor analysis of multimodal MRI, biofluid, and vascular biomarkers reveals latent constructs of brain health - Ella Rowsthorn; Ming Ann Sim; William T. O’Brien; Stuart J. McDonald; Katherine Franks; Benjamin Sinclair; Trevor T.-J. Chong; Stephanie Yiallourou; Marina Cavuoto; Lucy Vivash; Terence J. O’Brien; Xingfeng Shao; et al. (GeroScience, 2025)
Individual imaging and fluid biomarkers provide insights into specific components of brain health, but integrated multimodal approaches are necessary to capture the complex, interrelated biological systems that contribute to brain homeostasis and neurodegenerative disease. Using data from the Brain and Cognitive Health (BACH) cohort study ( N = 127; mean age = 67 years, 68% women), we performed an exploratory factor analysis to identify latent constructs of brain health. We included multimodal neurovascular imaging markers, brain atrophy metrics, plasma Alzheimer’s disease (AD) biomarkers, and cardiovascular risk factors. Five constructs emerged: “Brain & Vascular Health” (greater hippocampal volume, basal ganglia enlarged perivascular spaces (ePVS), cerebral blood flow, and HDL cholesterol; lower ventricle volume and BMI), “Structural Integrity” (greater cortical thickness, fractional anisotropy, and basal ganglia ePVS), “White Matter (WM) Fluid Dysregulation” (greater WM ePVS and Free Water), “AD Biomarkers” (higher phosphorylated tau [pTau]181 and pTau217; lower amyloid-beta 42/40 ratio), and “Neuronal Injury” (higher glial fibrillary acidic protein and neurofilament light chain). All constructs were associated with age (β = - 0.70–0.39, p ≤ 0.014), except for WM Fluid Dysregulation ( p > 0.05). Brain and Vascular Health and Structural Integrity (partial r = 0.305, p < 0.001) and AD biomarkers and neuronal injury (partial r = 0.248, p = 0.005) were positively correlated. Only Brain and Vascular Health was associated with global cognition (β = 0.27, SE = 0.13, p = 0.043). These findings provide a data-driven framework for examining distinct constructs underlying vascular health, fluid regulation, and neurodegenerative pathology. We demonstrate the utility of using multiple biomarkers to probe these biological systems, paving the way for future research to explore how these systems change across diverse neurodegenerative conditions. Graphical abstract

Fish as environmental sentinels for metal contaminants of human health concern in the Lower Mississippi River Basin - Scoty Hearst; Trent Selby; Joseph Kazery; Steven Everman; Manliang Feng; Lillian Sisson; Chinaza Nwaiwu; Alison Cevallos; James Lock; Matthew Sinclair (Journal of Trace Elements in Medicine and Biology, 2025)

Host response signature trends in persistent bacteraemia and metastatic infection due to Staphylococcus aureus and Gram-negative bacilli: a prospective multicentre observational study - Anna Maria Peri; Nastaran Rafiei; Kevin O’Callaghan; Anna Brischetto; Bianca Graves; Holly Sinclair; Matthew Eustace; Karen Lim; Jill Parkes-Smith; Adam Stewart; Natalie Davidson; Alexis Tabah; et al. (Infectious Diseases, 2024)

Grazing management for soil carbon in Australia: A review - Sarah E. McDonald; Warwick Badgery; Simon Clarendon; Susan Orgill; Katrina Sinclair; Rachelle Meyer; Dominique Bowen Butchart; Richard Eckard; David Rowlings; Peter Grace; Natalie Doran-Browne; Steven Harden; et al. (Journal of Environmental Management, 2023)

Polanyi adsorption potential theory for estimating PFAS treatment with granular activated carbon - Jonathan B. Burkhardt; Adam Cadwallader; Jonathan G. Pressman; Matthew L. Magnuson; Antony J. Williams; Gabriel Sinclair; Thomas F. Speth (Journal of Water Process Engineering, 2023)

Effects of a physical activity intervention on brain atrophy in older adults at risk of dementia: a randomized controlled trial - Benjamin Sinclair; Chris Steward; Vijay Venkatraman; Rowa Aljondi; Kay L. Cox; Kathryn A. Ellis; David Ames; Colin L. Masters; Pramit M. Phal; Matthew J. Sharman; Elizabeth V. Cyarto; Michelle M. Y. Lai; et al. (Brain Imaging and Behavior, 2021)

Myocardial Perfusion Simulation for Coronary Artery Disease: A Coupled Patient-Specific Multiscale Model - Lazaros Papamanolis; Hyun Jin Kim; Clara Jaquet; Matthew Sinclair; Michiel Schaap; Ibrahim Danad; Pepijn van Diemen; Paul Knaapen; Laurent Najman; Hugues Talbot; Charles A. Taylor; Irene Vignon-Clementel (Annals of Biomedical Engineering, 2021)
Patient-specific models of blood flow are being used clinically to diagnose and plan treatment for coronary artery disease. A remaining challenge is bridging scales from flow in arteries to the micro-circulation supplying the myocardium. Previously proposed models are descriptive rather than predictive and have not been applied to human data. The goal here is to develop a multiscale patient-specific model enabling blood flow simulation from large coronary arteries to myocardial tissue. Patient vasculatures are segmented from coronary computed tomography angiography data and extended from the image-based model down to the arteriole level using a space-filling forest of synthetic trees. Blood flow is modeled by coupling a 1D model of the coronary arteries to a single-compartment Darcy myocardium model. Simulated results on five patients with non-obstructive coronary artery disease compare overall well to [ $$^{15}$$ 15 O] $$\text {H}_{{2}}$$ H 2 O PET exam data for both resting and hyperemic conditions. Results on a patient with severe obstructive disease link coronary artery narrowing with impaired myocardial blood flow, demonstrating the model’s ability to predict myocardial regions with perfusion deficit. This is the first report of a computational model for simulating blood flow from the epicardial coronary arteries to the left ventricle myocardium applied to and validated on human data.

Seagrass Restoration Is Possible: Insights and Lessons From Australia and New Zealand - Yi Mei Tan; Oliver Dalby; Gary A. Kendrick; John Statton; Elizabeth A. Sinclair; Matthew W. Fraser; Peter I. Macreadie; Chris L. Gillies; Rhys A. Coleman; Michelle Waycott; Kor-jent van Dijk; Adriana Vergés; et al. (Frontiers in Marine Science, 2020)

A Systematic Review of How Multiple Stressors From an Extreme Event Drove Ecosystem-Wide Loss of Resilience in an Iconic Seagrass Community - Gary A. Kendrick; Robert J. Nowicki; Ylva S. Olsen; Simone Strydom; Matthew W. Fraser; Elizabeth A. Sinclair; John Statton; Renae K. Hovey; Jordan A. Thomson; Derek A. Burkholder; Kathryn M. McMahon; Kieryn Kilminster; et al. (Frontiers in Marine Science, 2019)

The Australian National Rabbit Database: 50 yr of population monitoring of an invasive species - Emilie Roy‐Dufresne; Miguel Lurgi; Stuart C. Brown; Konstans Wells; Brian Cooke; Greg Mutze; David Peacock; Phill Cassey; Dave Berman; Barry W. Brook; Susan Campbell; Tarnya Cox; et al. (Ecology, 2019)
With ongoing introductions into Australia since the 1700s, the European rabbit ( Oryctolagus cuniculus ) has become one of the most widely distributed and abundant vertebrate pests, adversely impacting Australia's biodiversity and agroeconomy. To understand the population and range dynamics of the species and its impacts better, occurrence and abundance data have been collected by researchers and citizens from sites covering a broad spectrum of climatic and environmental conditions in Australia. The lack of a common and accessible repository for these data has, however, limited their use in determining important spatiotemporal drivers of the structure and dynamics of the geographical range of rabbits in Australia. To meet this need, we created the Australian National Rabbit Database, which combines more than 50 yr of historical and contemporary survey data collected from throughout the range of the species in Australia. The survey data, obtained from a suite of complementary monitoring methods, were combined with high‐resolution weather, climate, and environmental information, and an assessment of data quality. The database provides records of rabbit occurrence (689,265 records) and abundance (51,241 records, >120 distinct sites) suitable for identifying the spatiotemporal drivers of the rabbit's distribution and for determining spatial patterns of variation in its key life‐history traits, including maximum rates of population growth. Because all data are georeferenced and date stamped, they can be coupled with information from other databases and spatial layers to explore the potential effects of rabbit occurrence and abundance on Australia's native wildlife and agricultural production. The Australian National Rabbit Database is an important tool for understanding and managing the European rabbit in its invasive range and its effects on native biodiversity and agricultural production. It also provides a valuable resource for addressing questions related to the biology, success, and impacts of invasive species more generally. No copyright or proprietary restrictions are associated with the use of this data set other than citation of this Data Paper.

A condition metric for Eucalyptus woodland derived from expert evaluations - Steve J. Sinclair; Matthew J. Bruce; Peter Griffioen; Amanda Dodd; Matthew D. White (Conservation Biology, 2018)
The evaluation of ecosystem quality is important for land‐management and land‐use planning. Evaluation is unavoidably subjective, and robust metrics must be based on consensus and the structured use of observations. We devised a transparent and repeatable process for building and testing ecosystem metrics based on expert data. We gathered quantitative evaluation data on the quality of hypothetical grassy woodland sites from experts. We used these data to train a model (an ensemble of 30 bagged regression trees) capable of predicting the perceived quality of similar hypothetical woodlands based on a set of 13 site variables as inputs (e.g., cover of shrubs, richness of native forbs). These variables can be measured at any site and the model implemented in a spreadsheet as a metric of woodland quality. We also investigated the number of experts required to produce an opinion data set sufficient for the construction of a metric. The model produced evaluations similar to those provided by experts, as shown by assessing the model's quality scores of expert‐evaluated test sites not used to train the model. We applied the metric to 13 woodland conservation reserves and asked managers of these sites to independently evaluate their quality. To assess metric performance, we compared the model's evaluation of site quality with the managers’ evaluations through multidimensional scaling. The metric performed relatively well, plotting close to the center of the space defined by the evaluators. Given the method provides data‐driven consensus and repeatability, which no single human evaluator can provide, we suggest it is a valuable tool for evaluating ecosystem quality in real‐world contexts. We believe our approach is applicable to any ecosystem.

Ancient chromosomal rearrangement associated with local adaptation of a postglacially colonized population of Atlantic Cod in the northwest Atlantic - Marion Sinclair‐Waters; Ian R. Bradbury; Corey J. Morris; Sigbjørn Lien; Matthew P. Kent; Paul Bentzen (Molecular Ecology, 2018)
Intraspecific diversity is central to the management and conservation of exploited species, yet knowledge of how this diversity is distributed and maintained in the genome of many marine species is lacking. Recent advances in genomic analyses allow for genome‐wide surveys of intraspecific diversity and offer new opportunities for exploring genomic patterns of divergence. Here, we analysed genome‐wide polymorphisms to measure genetic differentiation between an offshore migratory and a nonmigratory population and to define conservation units of Atlantic Cod ( Gadus morhua ) in coastal Labrador. A total of 141 individuals, collected from offshore sites and from a coastal site within Gilbert Bay, Labrador, were genotyped using an ~11k single nucleotide polymorphism array. Analyses of population structure revealed strong genetic differentiation between migratory offshore cod and nonmigratory Gilbert Bay cod. Genetic differentiation was elevated for loci within a chromosomal rearrangement found on linkage group 1 ( LG 1) that coincides with a previously found double inversion associated with migratory and nonmigratory ecotype divergence of cod in the northeast Atlantic. This inverted region includes several genes potentially associated with adaptation to differences in salinity and temperature, as well as influencing migratory behaviour. Our work provides evidence that a chromosomal rearrangement on LG 1 is associated with parallel patterns of divergence between migratory and nonmigratory ecotypes on both sides of the Atlantic Ocean.

Comment on ‘Seagrass Viviparous Propagules as a Potential Long-Distance Dispersal Mechanism’ by A. C. G. Thomson et al. - Elizabeth A. Sinclair; Renae Hovey; John Statton; Matthew W. Fraser; Marion L. Cambridge; Gary A. Kendrick (Estuaries and Coasts, 2016)

Multi-Scale Parameterisation of a Myocardial Perfusion Model Using Whole-Organ Arterial Networks - Eoin R. Hyde; Andrew N. Cookson; Jack Lee; Christian Michler; Ayush Goyal; Taha Sochi; Radomir Chabiniok; Matthew Sinclair; David A. Nordsletten; Jos Spaan; Jeroen P. H. M. van den Wijngaard; Maria Siebes; et al. (Annals of Biomedical Engineering, 2014)